Pengukuran Beban Kerja Fisik Dan Beban Kerja Mental Berbasis Ergonomi Terhadap Karyawan PT. Woneel Midas Leathers - Endang Widuri Asih; Widia Marselia; Cyrilla Indri Parwati; Arie Pohandry (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2022)
This research was conducted to determine how much physical workload and mental workload received by employees at PT. Woneel Midas Leathers, especially in the Quality Control (QC) department in carrying out their work. This research is a descriptive study, using a sample of 40 female employees who are the entire population of QC workers at PT. Woneel Midas Leathers. Data collection includes filling out the NASA-TLX questionnaire for mental workload analysis, and using employee physical data to calculate Body Mass Index (BMI) and pulse data calculated using the %CVL (Cardiovascular) method for physical workload analysis. The results of the calculation of the physical workload calculated using the %CVL (Cardiovascullar) method with an average physical workload of 31.62 employees are included in the